TRENDS IN THE DEVELOPMENT OF INTERNATIONAL TRADE IN 2011-2016, AND FORECASTS FOR 2017 - RĂDESCU, Octavian Dan (Theoretical and Practical Research in Economic Fields; Vol 8 No 1 (2017): TPREF, Volume VIII, Issue 1(15), Summer 2017DO - 10.14505/tpref.v7.1(15).03, 2017)
This paper analyzes the developments in world trade in goods and services in 2015 - 2016, as well as the prospects for 2017 - 2020. It highlights both the main determinants and salient features of merchandise trade in 2015, and its dynamics in terms of volume and value. It also sheds light on the geographical composition of merchandise trade and the major traders worldwide. Similarly, the paper outlines the main trends shaping trade in services in 2015. According to the findings of the paper, 2017 marked the sixth consecutive year in which trade growth has been disappointing, with trade expanding less than 3%, and exceeding only marginally global GDP growth.  All forecasts by international economic organizations in early 2016, leading to the conclusion that the expansion of international trade from 2016 to 2017 will grow moderately outrunning dynamic global GDP, still below the annual average rate recorded in the pre-crisis period.